2014
DOI: 10.1155/2014/468975
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium Isotherm Studies of Adsorption of Pigments Extracted from Kuduk-kuduk (Melastoma malabathricumL.) Pulp onto TiO2Nanoparticles

Abstract: The adsorption of natural pigments onto TiO2nanoparticles was investigated. The pigments were extracted from the dark purple colored pulp of the berry-like capsule of Kuduk-kuduk (Melastoma malabathricumL.). The Langmuir, Freundlich, Redlich-Peterson, and Sips isotherm models were used to analyze the equilibrium experimental data. Data correlated well with the Sips isotherm model, where the heterogeneity factor (n=0.24) indicated heterogeneous adsorption characteristics, with a maximum adsorption capacity of 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(34 citation statements)
references
References 30 publications
1
30
0
Order By: Relevance
“…However, the values of the maximum adsorption capacity obtained using the Sips model are comparable to that obtained by nonlinear Langmuir equation and have the same order (2 nitrophenol > 2,4 dinitrophenol and 4 nitrophenol). When n s = 1, the Sips equation reduces to the Langmuir equation (Kumara et al 2014).…”
Section: Three-parameter Isothermmentioning
confidence: 99%
“…However, the values of the maximum adsorption capacity obtained using the Sips model are comparable to that obtained by nonlinear Langmuir equation and have the same order (2 nitrophenol > 2,4 dinitrophenol and 4 nitrophenol). When n s = 1, the Sips equation reduces to the Langmuir equation (Kumara et al 2014).…”
Section: Three-parameter Isothermmentioning
confidence: 99%
“…The dimensionless heterogeneity factor 1/ n describes the heterogeneity of the material because 0.8025 is between 0 and 1. The value of 1/ n < 1 is related to the adsorption intensity constant that varies with the heterogeneity of the adsorbate . The adsorptive capacity was 40.11 mg g −1 for the removal of atrazine onto MBo.…”
Section: Resultsmentioning
confidence: 99%
“…where K R , a R and b are constants. Previous studies have shown that it is more accurate than the Langmuir and the Freundlich models, because it contains three tuning parameters (Kumara et al 2014).…”
Section: Adsorption Tests Of the Synthesized Magnetic Polymer Beadsmentioning
confidence: 99%